Long-term effectiveness of dobesilate in the treatment of papulopustular rosacea. (19th October 2011) - Cuevas, Pedro; Angulo, Javier; Giménez-Gallego, Guillermo
Abstract : This case report is a representative example from a study directed to assess the long-term clinical benefit of dobesilate in rosacea in five enrolled papulopustular rosacea patients with several years of disease, treated topically with 5% potassium dobesilate cream for 3 weeks. The patient suffered papulopustular rosacea for more than 10 years, during which she received topical metronidazole and azelaic acid, and systemic doxycycline therapies without satisfactory improvement. Dobesilate treatment promoted improvement of rosacea symptoms and signs. Two years after treatment the patient still shows a good facial cosmesis.